Consumption of very low-mineral water may threaten cardiovascular health by increasing homocysteine in children - Huang, Yujing; Tan, Yao; Wang, Lingqiao; Lan, Lan; Luo, Jiaohua; Wang, Jia; Zeng, Hui; Shu, Weiqun (Frontiers in Nutrition, 2023)
Introduction: Homocysteine (Hcy) is a critical factor for cardiovascular injury, and the elevation of Hcy in children will inevitably increase the risk of cardiovascular disease in adulthood. This study explored the effect of very low-mineral water on children's Hcy and cardiovascular health. Materials and Methods: This was a retrospective cohort study recruited two groups of 10–13-y-old children who had consumed direct drinking water (DDW) in school for four years. The NW group (119 boys, 110 girls) consumed normal DDW (conductivity 345 μs/cm). The VLW group (223 boys, 208 girls) consumed very low-mineral DDW (conductivity 40.0 μs/cm). Serum Hcy, Hcy metabolites, cofactors of Hcy metabolism, and cardiovascular biomarkers were assessed and standardized by age- and sex-specific Z-scores, and the differences between the two groups were analyzed with independent T-test. The relationships between Hcy metabolism biomarkers and key factors, cardiovascular biomarkers, serum Ca, and mineral intake were analyzed with linear regression. Results: Compared with the NW group, the VLW group had significantly higher serum Hcy, Apo-B, Apo-B/A1, and oxLDL, and lower serum 1,25,(OH)2D3, vitamin B6 and B12, 5-methyltetrahydrofolate, and Apo-A1. Serum Hcy was positively associated with serum Apo-B and Apo-B/A1, and negatively associated with Ca intake from water and serum 1,25,(OH)2D3. Conclusions: This study suggested that drinking very low-mineral water may increase Hcy level and oxidative stress, worsen lipid profile, and threaten the cardiovascular system in children. Reducing 1,25,(OH)2D3, and disordering of calcium metabolism might play important roles. This study first established an association between demineralized drinking water and cardiovascular health in children, suggesting a new environmental concern risk to cardiovascular health.